Civil Society, Cleavage Structures, and Democracy in Germany - Edgar Grande (German Politics, 2022)
This article analyses the consequences of recent changes in cleavage structures in German society for civil society, democracy, and social cohesion. It argues that the emergence of a new `demarcation-integration' cleavage has politicised civil society in Germany in several ways. As a result, the role of civil society for the future development of German democracy has become highly ambivalent. The article is organised into four parts. First, recent transformations in political conflict structures in Western European countries are outlined. Second, the article presents data on the manifestation of this conflict in Germany after the so-called `refugee crisis.' Third, the consequences of these new conflicts on civil society are analysed. Fourth, the relationship between civil society and democracy is discussed. The article concludes with suggestions for future research.
Keywords: 320